Genetic monitoring by rapd markers for repopulation programs of Salminus brasiliensis (Pisces, Characiformes) - doi: 10.4025/actascianimsci.v35i2.15904 - Fernanda Simões de Almeida; Carla Martins Lopes; Mário Luís Orsi; Rodolfo Nardez Sirol; Leda Maria Koelblinger Sodré (Acta Scientiarum. Animal Sciences, 2012)
The preservation of the genetic variability of hatchery stocks used to supplement naturalpopulations is a priority. Current study employed RAPD markers to examine the genetic diversity of douradosamples from the middle Paranapanema river and from the broodstock used in the stock enhancement programof the Aquaculture and Hydrobiology Station at the Salto Grande Hydroelectric Power Plant. Nineteen RAPDprimers were analyzed, which generated 299 bands and the latter were used for genetic analysis. The percentageof polymorphic fragments was higher in stock captured in the Paranapanema river than from fry stocks. Thegenetic diversity was lower in the broodstock than in natural population. Amova results showed that most interpopulationgenetic variation lay within stocks (83.9%) and not between them (16.1%). Moderate geneticdifferentiation (FST = 0.16) was reported. Nevertheless, differentiation decreased when the four fry stocks weremixed and analyzed as a single population (FST = 0.07). Instead of releasing each lot separately into the water,mixing specimens produced in the various fry stocks before releasing them in the river would be more feasible.The restocked population will have a genetic structure closer to natural populations.